The acquisition of 'To Be' as an auxiliary verb and a linking verb in the written work of Malaysian ESL learners - Farhanaz Bt. Mohd Baldev Shah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences , International Islamic University Malaysia, 2007)
The study investigated the acquisition of the English verb ‘to be’ by second language learners of English at the International Islamic University Malaysia (IIUM). The subjects were one hundred and sixty-eight students of the Bachelor of Human Sciences in English as a Second Language (BENL) programme. The study advocates a non-interventive as well as a non-experimental method of research, which applies discourse, textual and error analysis. The instruments used to gather the data were the subjects’ written essays and syntax tasks. The findings show that the subjects uniformly demonstrate a high preference in using ‘to be’ as a linking verb as opposed to the auxiliary verb. This means that sentences with auxiliary verb ‘to be’ do not appear as many as those with copula, in fact less than one third. The findings also reveal that the students’ proficiency level does affect the acquisition and use of ‘to be’, as the more proficient subjects produce more correct forms of ‘to be’, and the less proficient ones produce more incorrect ‘to be’ forms. The types of errors found to be committed include errors of addition, inflection, marker, omission, plurality/singularity, repetition, substitution, tense and word order. The most errors produced were those of plurality/singularity and inflection. Further syntactic analyses of the correct and incorrect production of ‘to be’ show that there are instances in which the structure of the explicit modals influences the production of ‘to be’ in the specific error types of addition and inflection namely. The research contributes to the dearth in overall research in this particular subject and to the teaching of English to ESL speakers.